# Calculate infinite summation of sin(x)/x [duplicate]

How do you calculate the infinite sum $\sum_{i=1}^{\infty} \frac{\sin(i)}{i}$? According to Wolfram Alpha, the value of the sum is $\frac{\pi - 1}{2}$, but it does not tell me the method by which it gets this result.

• Try the Poisson summation formula? Jan 26, 2018 at 5:17
• @HansLundmark, do you think you could elaborate a bit in an answer? Thanks.
– Alex
Jan 26, 2018 at 5:21
• See here: math.stackexchange.com/questions/1242280/…. (Set $y=0$ and consider only half of the sum, minus the zeroth term.) Jan 26, 2018 at 5:24
• Ah perfect, thanks for your help!
– Alex
Jan 26, 2018 at 5:27

Using the power series $$-\log(1-z)=\sum_{k=1}^\infty\frac{z^k}{k}$$ we get \begin{align} \sum_{k=1}^\infty\frac{\sin(k)}{k} &=\frac1{2i}\sum_{k=1}^\infty\frac{e^{ik}-e^{-ik}}{k}\\ &=\frac1{2i}\left[-\log(1-e^i)+\log(1-e^{-i})\right]\\ &=\frac1{2i}\log(-e^{-i})\\ &=\frac{\pi-1}{2} \end{align} That is, since $1-e^{-i}$ is in the first quadrant and $1-e^i$ is in the fourth, the imaginary part of $-\log(1-e^i)+\log(1-e^{-i})$ is between $0$ and $\pi$.
• We are evaluating a power series on the boundary of its convergence disk, or, equivalently, we are stating that the Fourier series of the sawtooth wave is pointwise convergent at $x=1$. That is true, but it needs a bit of extra care to be justified in full rigor (this applies to my old answer in the duplicate thread, too). Jan 26, 2018 at 20:31
Consider the two summations $$S=\sum_{k=1}^{\infty} \frac{\sin(k)}{k}\qquad \text{and} \qquad C=\sum_{k=1}^{\infty} \frac{\cos(k)}{k}$$ $$C+iS=\sum_{k=1}^{\infty} \frac{\cos(k)+i \sin(k)}{k}=\sum_{k=1}^{\infty} \frac{e^{i k}} k=\sum_{k=1}^{\infty} \frac{(e^{i})^ k} k=-\log \left(1-e^i\right)$$ $$C-iS=\sum_{k=1}^{\infty} \frac{\cos(k)-i \sin(k)}{k}=\sum_{k=1}^{\infty} \frac{e^{-i k}} k=\sum_{k=1}^{\infty} \frac{(e^{-i})^ k} k=-\log \left(1-e^{-i}\right)$$ Expanding the logarithm $$C+i S=-\frac{1}{2} \log \left(\sin ^2(1)+(1-\cos (1))^2\right)+i \tan ^{-1}\left(\frac{\sin (1)}{1-\cos (1)}\right)$$ $$C+i S=-\frac{1}{2} \log (2-2 \cos (1))+i \left(\frac{\pi }{2}-\frac{1}{2}\right)$$ $$C-i S=-\frac{1}{2} \log \left(\sin ^2(1)+(1-\cos (1))^2\right)-i \tan ^{-1}\left(\frac{\sin (1)}{1-\cos (1)}\right)$$ $$C-i S=-\frac{1}{2} \log (2-2 \cos (1))+i \left(\frac{1}{2}-\frac{\pi }{2}\right)$$ $$C=\frac{(C+iS)+(C-iS)}2=-\frac{1}{2} \log (2-2 \cos (1))$$ $$S=\frac{(C+iS)-(C-iS)}{2i}=\frac{1}{2} (\pi -1)$$